A4_2 This Barbie is Radioactive - Savic, Natasha; Birch, Hannah; Tzabach, Lee (Physics Special Topics, 2023)
In this paper, we investigate how many Barbies are required to absorb the energy of Oppenheimer’s atomic bomb developed in the Manhattan Project. To do this, we calculate the latent heat of one Barbie to determine how much energy one is able to endure before melting. We find that, to fully absorb the energy from Oppenheimer’s atomic bomb, we would need roughly 4.64 billion Barbies.